Principles and Applications of Magnetic Particle Imaging - Gleich, Bernhard (Aktuelle Forschung Medizintechnik - Latest Research in Medical Engineering, 2014)
Bernhard Gleich introduces Magnetic Particle Imaging (MPI) including all aspects that are necessary for a complete understanding. MPI is a new imaging modality invented by Bernhard Gleich and Jürgen Weizenecker. The method is capable of imaging the distribution of superparamagnetic iron oxide particles (SPIOs) with high sensitivity, high spatial resolution, and high imaging speed. The author summarizes the results of a number of original papers and countless innovations he has elaborated in the young discipline of magnetic particle imaging. Contents ·         Medical imaging methods ·         Magnetic Particle Imaging ·         Magnetic nanoparticles  Target groups ·         Academics, scholars, and experts in the field of medical engineering, esp. magnetic particle imaging  Author Dr. Bernhard Gleich works as a senior scientist at an electronics and medical imaging company in Hamburg. Editors The series Aktuelle Forschung Medizintechnik is edited by Thorsten Buzug.